Indigenous Māori perspectives of smokefree parks - Robin Quigg; Louise Marsh; Bobbi Clark‐Heu (Elsevier, 2022)
Abstract Objective: This study aims to understand the context of place associated with smoking in urban Hamilton parks from a Te Ao Māori perspective (the worldview of Māori, the Indigenous people of Aotearoa New Zealand). Methods: Our study approached smokefree environments in Hamilton through a Māori lens, undertaking interviews with family groups and people from organisations involved in the local Smokefree environments policy. Results: The majority of the 26 adult participants identified as Māori, with 30% being current smokers. Parks had a place in the sporting memories of participants. Smoking was merged with these memories. Important features of places that influenced smoking behaviours were raised, with signage a key talking point. Conclusions: The colonial construct of parks do not make visible Māori values and historical associations with the land, nor do they set a framework that would promote Māori ways of being and doing, including enacting smokefree spaces and places. Implications for public health: This study provides the incentive to address change in parks and reserve management that would support Māori aspirations for their health and wellbeing associated with ancestral land, and give meaning to smokefree environments.